Course of Care of a Multiple Sclerosis Patient in the Context of Pharmacotherapy - Anna Smelkowska; Maria Wilkiewicz; Barbara Grabowska-Fudala; Krystyna Jaracz (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2015)
Multiple sclerosis (SM) is an incurable, advancing, demyelinating illness with inflammatory background. It constitutes the most frequent cause of disability among young people, between 20 and 40 years of age. Despite the identification of multiple factors causing the disease, its pathomechanism has not been yet completely discovered. For this reason, finding an effective cure for multiple sclerosis continues to present a challenge (for modern scientists). The currently available treatment for SM aims to halt its progress and to minimalize complications related to the disease. The goal of the work was to provide an overview of the therapies currently available to those suffering from SM. Selecting an appropriate form of treatment and medication as well as preparing the patient and continuation of monitoring during the therapy constitute important elements of conducting an effective SM therapy. (JNNN 2015;4(3):130–137)